Program Pendidikan Kecakapan Hidup Bagi Anak Usia Fase A - Ela Susilawati; Saiful Falah; E Mujahidin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Imam Al-Ghazali defined that education is the perfection of life in this world and the hereafter. Thus, humans who want to achieve perfection in life in this world and the afterlife must have religious knowledge. Religious knowledge is so important for provision in life, without religious knowledge humans can be said to be far from perfection. Apart from religious knowledge, life skills education is also very important for provisions in life. However, it is very unfortunate that many children who are teenagers or are about to enter puberty do not yet have mature life skills in terms of personal skills and social skills. From KPAI (Indonesian Child Protection Commission) data during January - November 2023, 37 children ended their lives. Self-harm behavior and attempts to end life are major global mental health problems due to their increasing frequency. This case occurred at a vulnerable age (grade 5-6 of elementary school), grade 1 or 2 of junior high school, grade 1.2 of high school. Another case related to juvenile delinquency is the incident involving the death of a student in Bogor which sadistically adds to the number of delinquencies among students. It also leaves a red report card for the world of education, because the sadistic incident was carried out by students. From this background, it is necessary to have a program that will strengthen children's life skills education from pre-adulthood, especially phase A, so that class children can be ready to live life in the next phases. This research uses the Research and Development (R&D) method with the ADDIE model, namely Analyze, Design, Development, Implementation, Evaluation. The program needs analysis was carried out by creating a Google form with a closed questionnaire which was distributed randomly to ten respondents. After the needs analysis, the researcher analyzed previous programs. There were two programs that the researcher used as a reference, namely the entrepreneurship program and the self-help program in an effort to increase independence. then the next step is to design the program, the programs prepared by the researchers are as follows: cookies (cooking with kids), market day, BTS (Bed Time Sirah), PKS (Student Independence Habits), PMO (Habits of Helping Parents) and CLMH (Love of the Environment and Living Creatures). After the program was prepared, it was validated by several experts including Islamic religious education experts, language experts and also child psychology experts. After going through expert validation, the program is implemented to users. After implementation, the final stage is to test the feasibility through evaluation. The feasibility test is carried out by experts by providing an assessment of the program being prepared. From the results of this feasibility test, it was found that this program was good and suitable to be applied to pre-age children, especially in phase A in the life skills education process.